(untitled) (Eurasian Journal of Ecology, 2019)
In order to increase the fish productivity of water bodies and the rational use of aquatic animals in Kazakhstan, acclimatization events have been repeatedly held. Acclimatization work touched almost all the reservoirs of the republic, including the mountain. The peculiarity of abiotic indicators of mountain reservoirs impoverishes the species diversity of aquatic organisms, and in order to increase biodiversity and rational use of the reservoir, rainbow trout was brought. In the middle of the 20th century, rainbow trout from reservoirs was acclimatized to the Kolsay lakes. Currently, several aboriginal species inhabit the pond, but only rainbow trout is of commercial importance. The paper presents data on the current state of rainbow trout Parasalmo mykiss (mikizha), analyzed materials for several years. According to the results of biological indicators, it was revealed that the main dimensional weight indicators remain stable. The significance of biological traits on the lower Kolsay lake is higher compared to the average Kolsay. The research catch was both young and old-aged individuals of fish, large individuals are not found annually. The food supply for fish is sufficient, as evidenced by the data on fatness. Key words: acclimatization, rainbow trout, Kolsay lake, native species, biological features